Re-Irradiation With Stereotactic Body Radiotherapy for In-Field Recurrence of Pancreatic Cancer After Prior Stereotactic Body Radiotherapy: Analysis of 24 Consecutive Cases - Shen, Yuxin; Zhu, Xiaofei; Cao, Fei; Xie, Hongliang; Ju, Xiaoping; Cao, Yangsen; Qing, Shuiwang; Jia, Zhen; Gu, Lei; Fang, Fang; Zhang, Huojun (Frontiers in Oncology, 2021)
Purpose/Objectives: Locally recurrent pancreatic cancer is a therapeutic challenge and aggressive approaches are needed to improve its clinical outcomes. Stereotactic body radiotherapy (SBRT) is a promising treatment for pancreatic cancer with an excellent local control and acceptable toxicity. However, the safety and efficacy of SBRT for in-field recurrence after initial SBRT remains unknown. The aim of the study was to investigate the feasibility of re-irradiation with SBRT for locally recurrent pancreatic cancer after prior definitive SBRT. Material/Methods: Twenty-four consecutive patients with pancreatic cancer received two courses of SBRT in our center between January 2014 and December 2016. The median prescription dose of the initial and second course of SBRT was 35.5Gy/5-7f and 32Gy/5-8f respectively. Clinical outcomes including overall survival (OS), disease control and toxicity were evaluated after treatment. Results: The median interval between two courses of SBRT was 13 months (range: 6-29 months). From the first SBRT, the median OS of 18 patients with limited diseases was 26 months (95% confidence interval, CI: 19.1-32.95 months). The median OS of 12 patients without metastasis was 14 months (95% CI: 10.6-17.4 months) from re-irradiation of SBRT. The overall response rate and disease control rate was 50%, 13% and 100%, 86.9% after each SBRT, respectively. CA19-9 levels declined dramatically after re-irradiation within 1 month (P=0.002) and 3 months (P=0.028). Twelve (75%) out of 16 patients had pain relief after re-irradiation. None of the patients experienced gastrointestinal toxicity. Conclusions: Re-irradiation with SBRT can provide favorable outcomes and effective analgesia with mild toxicity after prior SBRT for in-field recurrent pancreatic cancer, which might be feasible for locally relapsed pancreatic cancer.